profile
Опубликовано 11 месяцев назад по предмету Математика от aliannam

Найдите значение выражения:

А) - (1 - x) - (5,1 + x) =

B) - (a - x - 3) - (x - a + 2) =

C) (a + 3,3 - a) - (3,3 + x) =

D) - (2,43 + x - b) - (2,43 + b - x) =

E) - (1,53 - x + 1) - (x - a - 2,53) =





Найдите значение выражения:

А) -(a - x) - (5,1 + x) + a - 5,1 =

B) (b - x) - (a - x) + (a - b) =

C) -(a + 3,3) - (x - a) - 3,3 + x =

D) (2,43 + 1,1) - (b + 2,43) + (b - 1,1) =

E) - (1,53 - x + a) - (x - 1,53 - a) - a =








  1. Ответ
    Ответ дан krugly1981
    А) - 1 + x - 5,1 - x = - 6,1
    B) - a + x + 3 - x + a - 2 = 3 - 2 = 1
    C) a + 3,3 - a - 3,3 - x = - x
    D) - 2,43 - x + b - 2,43 - b + x = - 4,86
    E) - 1,53 + x - 1 - x + a + 2,53 = a - 2,53 + 2,53 = a

    A) -a + x - 5,1 - x + a - 5,1 = - 10,2
    B) b - x - a + x + a - b = 0
    C) -a - 3,3 - x + a - 3,3 + x = - 6,6
    D) 2,43 + 1,1 - b - 2,43 + b - 1,1 = 0
    E)  - 1,53 + x - a - x + 1,53 + a - a = - a